Pengembangan model pembelajaran Pendidikan Agama Islam konstruktivistik bermetode hiwar qishashi pada Siswa Kelas VII di MTs Mujahidin Sooko Mojokerto - Muhammad Munib (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Constructivism learning is one of the models of learning process that states in the learning process begins with creating cognitive conflict. The objectives of this research are: To make the learning model of Constructivist Islamic Education using hiwar qishashi in class VII students in MTs Mujahidin Sooko Mojokerto. Result of research Development of learning model of Constructivist Islamic Education bermetode hiwar qishashi on Student Class VII in MTs Mujahidin Sooko Mojokerto this is as follows. 1) Product revised based on theoretical and empirical test results are: Revision by Student by questionnaire: (1) improve the use of resources in applying the model (2) Change the way of evaluation in the use of the model (3) Improve the model appearance or change the learning strategy. 2) The developed product is attractive for classroom learning in a classical and independent manner. 3) This product product  can ease the burden of teacher in teaching. 4) The result of expert validation and trial, Constructivistic Learning Model hiwar qishashi is feasible to be used for the subject of Islamic Religious Education. 5) The product developed can improve students' learning motivation, and motivation is one of the requirements of the implementation of productive learning model.